Conference Proceedings of The Philosophy of Computer Games 2008 - Günzel, Stephan; Liebe, Michael; Mersch, Dieter (Potsdam University Press, 2009)
This first volume of the DIGAREC Series holds the proceedings of the conference The Philosophy of Computer Gamesʺ, held at the University of Potsdam from May 8-10, 2008. The contributions of the conference address three fields of computer game research that are philosophically relevant and, likewise, to which philosophical reflection is crucial. These are: ethics and politics, the action-space of games, and the magic circle. All three topics are interlinked and constitute the paradigmatic object of computer games: Whereas the first describes computer games on the outside, looking at the cultural effects of games as well as on moral practices acted out with them, the second describes computer games on the inside, i.e. how they are constituted as a medium. The latter finally discusses the way in which a border between these two realms, games and non-games, persists or is already transgressed in respect to a general performativity.
Google-Books-ID: SJ972ia4kZQC
Keywords: 1-Jeux vidéo; _Nettoyé

Différance at Play. Unfolding Identities Through Difference in Videogame Play - Mitsuishi, Yara (Conference Proceedings of The Philosophy of Computer Games 2008, 2009)
This paper approaches the debate over the notion of “magic circ-le” through an exploratory analysis of the unfolding of identities/differences in gameplay through Derrida’s différance. Initially, différance is related to the notion of play and identity/difference in Derrida’s perspective. Next, the notion of magic circle through Derrida’s play is analyzed, emphasizing the dynamics of diffé-rance to understand gameplay as process; questioning its boun-daries. Finally, the focus shifts toward the implications of the interplay of identities and differences during gameplay.
Google-Books-ID: SJ972ia4kZQC
Keywords: 1-Jeux vidéo; 2-Étude des représentations; 5-Autrice; _Nettoyé

Gameplay in the “Zone of Becoming”: Locating Action in the Computer Game - Mukherjee, Souvik (Conference Proceedings of The Philosophy of Computer Games 2008, 2009)
Extending Alexander Galloway’s analysis of the action-image in videogames, this essay explores the concept in relation to its source: the analysis of cinema by the French philosopher Gilles Deleuze. The applicability of the concept to videogames will, therefore, be considered through a comparison between the First Person Shooter S.T.A.L.K.E.R. and Andrey Tarkovsky’s film Stalker. This analysis will compellingly explore the nature of videogame-action, its relation to player-perceptions and its loca-tion within the machinic and ludic schema.
Google-Books-ID: SJ972ia4kZQC
Keywords: 1-Cinéma; 1-Jeux vidéo; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé